'I saw it on Facebook!' Assessing the influence of social media on patient presentation to a melanoma screening clinic. (2nd November 2019) - Guckian, J.; Jobling, K.; Oliphant, T.; Weatherhead, S.; Blasdale, K.
Summary: Background: The motivations for patients presenting to melanoma screening clinics (MSCs) with concerning skin lesions are poorly understood. Social media (SoMe) refers to online platforms designed to facilitate sharing of information with billions of users worldwide. There is evidence of patients posting skin lesion 'selfies' on SoMe, influencing internet searches. Interventions through SoMe may have positive impacts on health seeking behaviour. Aim: To identify the influence of SoMe on patients presenting to an MSC service, and to establish whether patients have been exposed to SoMe posts on skin cancer, from medical authorities or the public. Method: For this pilot study, qualitative data were collected from patient questionnaires over 7 consecutive weeks at MSCs in Newcastle upon Tyne hospitals. Questions involved demographics, factors influencing attendance, use of SoMe and exposure to content on skin lesions on SoMe. Results: Questionnaires were collected from 249 patients across a range of ages. Self‐examination of lesions was the most common driver. One person in the study population described SoMe as having motivated their attendance, while 30 patients recalled seeing posts from health authorities regarding skin cancer. Qualitative data indicated that patients could be influenced by targeted public health campaigns on SoMe. Conclusions: This study suggests that SoMe is not currently a major conscious driver to attend an MSC, even among SoMe‐familiar populations. However, the fact that SoMe is ubiquitous in society, in conjunction with our qualitative data, may suggest that current strategies for SoMe melanoma information delivery are not of requisite quality to break through to target populations.